A Facile Method for the Fabrication of Luminescent Eu3+-Doped SiO2 Nanowires - Fei Gao; Xinyu Zhao; Jinglin Liu (Gels, 2022)
Europium trivalent ion (Eu3+)-doped silica nanowires were prepared, and the positioning of Eu3+ in the silicon dioxide nanowire matrix was researched. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction analysis (XRD) and energy-dispersive X-ray spectroscope analysis (EDX) were used to characterize the product’s morphology and structure. The representation of Fourier transform infrared spectra (FT-IR) and X-ray photoelectron spectroscopy (XPS) were indicative of the presence of a covalent Eu-O-Si bond. The results suggest that Eu3+ was successfully doped into amorphous silica. Furthermore, a sol-gel inorganic−organic co-assembly mechanism model was proposed to illuminate the formation of the rare-earth ion-doped nanowires. In addition, photoluminescent emission of europium ions in a silica matrix was further discussed. It was demonstrated that a 10% content of Eu3+ resulted in a quenching effect and after annealing at 650 °C, the europium ions in the nanowires had a high luminescence intensity due to the silica network structure.